Joyful Learning Berbasis Ice Breaking Dalam Pembelajaran Mufradat di MTs Singosari - Sakinah Naziha; Laily Fitriani (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2023)
Strategies in mufradat learning at the MTs level play an important role in supporting learning success. This study aims to determine the process of applying Joyful Learning based on Ice Breaking in mufradat learning at MTs El-Jasmeen and the student's responses. This study uses a qualitative descriptive approach. The primary data sources of this research are the results of observations, interviews, and documentation of teachers and students. In addition, research will be supported by secondary data sources in the form of scientific articles or books related to the discussion. Data collection techniques used are observations, interviews, and documentation. All collected data were analyzed in four stages: collection, condensation, presentation, and conclusion. For the validity of the data, the researcher triangulated the data at the end of the study. The results of this study are (1) In mufradat learning, Joyful Learning is carried out by incorporating ice-breaking and using existing technology. 2) The response of all students is good, and they feel happy with the existing learning.